Tacrolimus Improves Therapeutic Efficacy of Umbilical Cord Blood-Derived Mesenchymal Stem Cells in Diabetic Retinopathy by Suppressing DRP1-Mediated Mitochondrial Fission - Hang Hyo Jo; Yeong Seok Goh; Hye Jih Kim; Dae Hyun Kim; Hyemin Kim; Jiyi Hwang; Ji Seung Jung; Nanyoung Kang; Sang Eun Park; Kyung Mee Park; Hyun Jik Lee (MDPI AG, 2023)
Diabetic retinopathy (DR) is a leading cause of blindness in diabetic patients. Umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) are emerging as a promising new drug for degenerative disease associated with diabetes. Recent studies have shown that high glucose-increased excessive calcium levels are a major risk factor for mitochondrial reactive oxygen species (mtROS) accumulation and apoptosis. This study aimed to investigate the role of high glucose-induced NFATC1 signaling in mitochondrial oxidative stress-stimulated apoptosis and the effect of tacrolimus on the therapeutic efficacy of subconjunctival transplantation of UCB-MSCs in a DR rat model. High glucose increased mtROS and cleaved caspase-9 expression in UCB-MSCs. High glucose conditions increased O-GlcNAcylated protein expression and nuclear translocation of NFATC1. Tacrolimus pretreatment recovered high glucose-induced mtROS levels and apoptosis. In the DR rat model, subconjunctival transplantation of tacrolimus-pretreated MSCs improved retinal vessel formation, retinal function, and uveitis. In high glucose conditions, tacrolimus pretreatment reduced protein and mRNA expression levels of DRP1 and inhibited mitochondrial fission. In conclusion, we demonstrated that high glucose-induced O-GlcNAcylation activates NFATC1 signaling, which is important for DRP1-mediated mitochondrial fission and mitochondrial apoptosis. Finally, we proposed NFATC1 suppression by tacrolimus as a promising therapeutic strategy to improve the therapeutic efficacy of UCB-MSC transplantation for DR treatment.